Carotid plaque fissure: An underestimated source of intraplaque hemorrhage. (November 2016) - Daemen, Mat J.; Ferguson, Marina S.; Gijsen, Frank J.; Hippe, Daniel S.; Kooi, M. Eline; Demarco, Kevin; van der Wal, Allard C.; Yuan, Chun; Hatsukami, Thomas S.
Abstract: Background and aims: Plaque fissuring, a phenomenon morphologically distinct from the classical rupture of a thinned fibrous cap, has not been well characterized in carotid atherosclerosis. The aim of this study was to establish the prevalence of plaque fissures in advanced carotid plaques with an otherwise intact luminal surface, and to determine whether they might be a source of intraplaque hemorrhage (IPH). Methods: We evaluated 244 surgically intact, 'en bloc' embedded, serially sectioned carotid endarterectomy specimens and included only those plaques with a grossly intact luminal surface. Results: Among the 67 plaques with grossly intact luminal surface, cap fissure was present in 39 (58%) plaques. A total of 60 individual fissures were present, and longitudinally mean fissure length was 1.3 mm. Most fissures were found distal to the bifurcation (63%), proximal to the stenosis (88%), and in the posterior (opposite the flow divider) or lateral quadrants (80%). 36% of the fissures remained in the superficial third of the plaque. 52% extended from the lumen surface to the middle third of the plaque and 12% reached the outer third of the plaque on cross section. Fissures often occurred between two tissue planes and were connected to IPH (fresh: 63%; any type: 92%) and calcifications (43%). No correlation was found with patient characteristics such as symptom status, carotid stenosis, hypertension, diabetes, smoking and medications (statins or antiplatelet agents). Conclusions: Plaque fissures are common in advanced carotid plaques with an otherwise grossly intact luminal surface and are associated with fresh intraplaque hemorrhage. As they occur on the interface between plaque components with different mechanical properties, further biomechanical studies are needed to unravel the underlying failure mechanisms. Highlights: Plaque fissures are very common in advanced carotid plaques and are associated with intraplaque hemorrhage. Plaque fissures occur on the interface of plaque components. Delamination, that is biomechanical failure between layers with different tissue properties, is causing plaque fissuring.